Cuidados de enfermagem a vitima de acidente vascular cerebral (AVC) - Silva, Dilson Nobre da (Universidade Federal do Tocantins, 2021)
Stroke is a transient or definitive neurological deficit in a brain area secondary to vascular injury, with rapid development of clinical signs due to local or global disturbances of brain function lasting longer than 24 hours, causing limitations to the individual for exercise daily activities and rehabilitation. The aim of the study was to perform the systematization of nursing care to a patient with stroke sequelae. This is a literary review for the identification of nursing care and assistance appropriate for patients affected by stroke. The search for scientific articles occurred in indexed databases such as: Academic Google, PubMed, Scieloand Google Academic, using the descriptors: Stroke, Nursing Diagnosis, Nursing Care, Care. The inclusion criteria in this review were: articles published between 2012 and 2019, freely available in Portuguese in the databases that address the theme of the study. Articles that did not fit the inclusion criteria were excluded.